Hydrological consequences of armed conflicts and massive migrations in the Lower Mekong Basin over the second half of the 20th Century. [Abstract only]. - Lacombe, Guillaume; Pierret, Alain; Hoanh, Chu Thai; Sengtaheuanghoung, Oloth (2010)
We investigated whether the Vietnam War bombing and conflict-induced exodus could have altered the hydrological behaviour of the Mekong Basin. The rainfall-runoff relationship was analysed in 2 catchments over period 1960-2004 (figure 1). In each catchment, rainfall and runoff time series together with potential evapotranspiration were used as input to run GR2M monthly water balance model whose robustness is adapted to data-scarce conditions. The space-time distribution of densities of bombs dropped during the war was derived from UXO-NRA database which records the amount and type of ordnances and the aircraft types and numbers per US Air Force sorties from 1965 to 1973. Bomb-induce damages inflicted on vegetation was estimated using the Bomb Damage Assessment Report. We found that the delivery of about 1.5 million tons of high-explosive ordnances likely caused profound damage to one third of the southern catchment whose runoff increased by >365 mm/year during at least 4 years after bombing climaxed in 1972. The magnitude of this increase was found to be consistent with usual tropical forest transpiration rates over the bomb-cleared surface area. No hydrological change was observed during this period in the 30-fold-less bombed catchment located in the North. From 1995 onward, southern and northern catchments' runoff productions are significantly higher and lower than in pre-war conditions, respectively. These hydrological shifts are most likely attributed to permanent changes in the vegetation cover, either denser in the northern sub-catchment (in response to the extensive abandonment of cultivated lands) or sparser in the southern catchment (as a result of bomb-degraded soil conditions). These results illustrate the high responsiveness of flow regime to forest cover changes in tropical areas where deforestation is expected to perpetuate at a high rate over the coming decades.